PENDEKATAN MAQASHID AL-SYARIAH SEBAGAI METODE PENGGALIAN HUKUM ISLAM - Hafidz Miftahuddin, Abdul; Mariyatul Qibtiyah, Ulfa (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
Maqashid al-Sharia are legal provisions prescribed by Allah for the benefit of mankind. The general purpose of making sharia or law is to realize benefits for humans in this life, either by obtaining benefits for them, by rejecting the harm from themselves. The division of maqashid sharia can be seen from various aspects, namely from the objectives there are maqashid al-syari and maqashid al-mukallaf. Judging from the needs and their influence on the law there are maqashid al-dharuriyyat, al-hajiyyat, and al-tahsiniyyat. Judging from the scope, there are maqashid al-ammah, maqashid al-khassah, and maqashid al-juziyyah. Judging from the strength there are al-maqashid al-qatiyyah, al-maqashid al-zanniyyah, al-maqashid al-wahmiyah.